Colon cancer with bone marrow metastasis concurrent with disseminated intravascular coagulation syndrome: Case report - Sema YILMAZ; Ömer ÖZÜTEMİZ and Murat ALKANAT (Turkish Journal of Gastroenterology, 2019)
-